İslam hukuku açısından savcılık kurumu - Türkyılmaz, Özlem (My University, 2022)
İnsan; bireyselde fıtratı gereği, toplumsal düzende de huzurun müsebbibi olarak adalete hep ihtiyaç duymuştur. Devletler de adaleti sağlama adına hukuklarını geliştirmiş, eksik sujelerini ve uygulamalarını da zaman içerisinde tamamlamışlardır. Kanunlar, adli teşkilat, yargı unsurları vs hep adalete ulaştırmayı amaçlayan hukuk düzeni için ortaya konmuş ürünlerdir. Bu çalışmada da adaleti sağlamada en önemli faktörlerden olan adli teşkilatın bir unsuru “savcılık” müessesesi ele alınacaktır. “Savcılık” kurumunun; İslam Hukukundaki tarihi gelişimini, nazariyedeki konumunu, fonksiyonunu ve önemini ortaya koymayı amaçlayan bu çalışma; savcılık konusunda farklı bağlamlarda ve genişlikte yazılmış eser ve çalışmaların bir özeti olması ve konuyu “İslam Hukuku” özelinde Türkçe olarak ele alması açısından önemlidir.

Human is a social entity. While living in society, he was always needed justice due to his nature. Because justice is the building block of social order. States have also developed their laws to ensure justice and have completed their deficiencies over time. When viewed from this aspect; laws, judge organisations and judicial elements are the items of legal order which aims to provide justice. In this study, the “Institution of Prosecution”, which is one of the most important elements in the provision of justice, will be examined. This study which aims to reveal the historical development of the institution of prosecution in Islamic law, its position in theory, its function and importance, is important in terms of being a summary of the studies about the prosecution written in different contexts and in different widths, and examining the subject in Turkish, in terms of “Islamic law.”
Keywords: Islamic law; İslam hukuku; Judgment; Kamu Hukuku; Prosecution; Public law; Public Prosecutor; Savcı Islamic law; Savcılık; Yargı